O incidente de resolução de demandas repetitivas no ordenamento jurídico brasileiro - Mortati, Lucas Cavina Mussi (2021)
The existence of different judgments for identical crises of law, in the same historical moment, cannot have space in face of the fundamental guarantee of democracy, in which everyone must be equal before the law. In an attempt to solve this wounds of the Judiciary, there were a series of legislative innovations, not only in Brazil, that agitated the legal community. One of them was the creation of the repetitive claims resolution incident. Within this reality, this study seeks to systematically analyze the aforementioned institute, starting from the inspiration for its creation, addressing its controversial legal nature, going through the intricate discussion about its constitutionality, as well as analyzing its main aspects, such as: assumptions of admissibility, standing, competente jurisdiction, procedure, application and onverruling of the precedent. A systematic and finalistic interpretation of the rules related to this mechanism is presented, which the result of a thorough analysis of the legal system and doctrine, which, in the end, makes it possible to glimpse the legitimacy and effectiveness of the institute in realize its main purpose (legal certainty and equal protection), in addition to the achievement of secondary objectives (principle of speedy trial and procedural economy)